Polish Americans in the History of Bilingual Lexicography: The State of the Art - Podhajecka, Mirosława (Lexikos, 2018)
This paper measures dictionaries made by Polish Americans against the development of the Polish–English and English–Polish lexicographic tradition. Of twenty nine monoscopal and biscopal glossaries and dictionaries published between 1788 and 1947, four may be treated as milestones: Erazm Rykaczewski's (1849–1851), WÅ‚adysÅ‚aw Kierst and Oskar Callier's (1895), WÅ‚adysÅ‚aw Kierst's (1926–1928), and Jan StanisÅ‚awski's (1929). Unsurprisingly, they came to be widely republished in English-speaking countries, primarily the United States of America, for the sake of Polish-speaking immigrants. One might therefore wonder whether there was any pressing need for new dictionaries. There must have been, assuming that supply follows demand, because as many as eight Polish–English and English–Polish dictionaries were compiled by Polish Americans and published by the mid-twentieth century. The scant attention accorded this topic suggests a chronological approach to these dictionaries is in order, firstly, to blow the dust from the tomes; secondly, to establish their filial relationships; and, lastly, to evaluate their significance for the bilingual dictionary market.